PEMBELAJARAN LIFESKILL DAN PRESTASI BELAJAR SEBAGAI PENDORONG MINAT BERWIRAUSAHA - Dharmosamoedero, Djati Poetryono (TALENTA, 2015)
Entrepreneurship is a supporting factor that determines the reciprocation of the economy of a country. For college graduates be given with knowledge and skills should dare to create their own jobs to take advantage of its knowledge and skills in accordance with their respective fields. By teaches entrepreneurship at each vocational field, the students are expected after graduation is able to develop the business world to create their own jobs in accordance with their skills, thus the interest in entrepreneurship in students need is grown. Interest in entrepreneurship include: willingness to work hard and diligently to achieve its business progress, the willingness to bear the various risks associated with the action sought is doing, willing to take the path and a new way, a willingness to live frugally, a willingness to learn from failures. The ability of existing skills and learning achievement that will either be able to create an interest in entrepreneurship.